VOLCANOSTRATIGRAPHY AND PETROGENESIS OF BANDA API VOLCANO AND SURROUNDINGS, CENTRAL MALUKU, MALUKU PROVINCE - Edbert Manurung, Aland
Banda Api Volcano is one of active volcanoes which located at Banda Arc. Banda Archipelago have undergone at least two stages of caldera formation: Lonthoir and Neira Calderas. Volcanostratigraphy and petrogenesis can give information about formation of the volcano, magmatism, magma series, and evolution of the tectonic settings of calderas and volcano of the Banda Archipelago. There are six eruption phases that built up the Banda Archipelago: early Lonthoir pre-caldera, late Lonthoir pre-caldera, Neira pre-caldera, Neira post-caldera, Banda Api volcano formation, and Banda Api flank eruption. Within calderas and volcano, magma differentiation processes that occur are fractional crystallization at the three volcanoes, assimilation at Lonthoir and Neira Caldera, and magma mixing at Neira and Banda Api. Magmatic processes are derived from plagioclase microtexture in which it shows that magma ascent decompression and magma chamber convection occur at the three volcanoes, while syn-eruption decompression only occurs at Lonthoir and undercooling process only occurs at Neira and Banda Api. Rare Earth Elements (REE) of Banda Archipelago are depleted in comparison with calcalkaline magma and suit with basalts from island arc tectonic setting. Most of lava samples have up to 10 percent phenocrysts, no alkali feldspar, glassy groundmass, low K2O content, and iron enrichment at early stage of differentiation, which is the character of island arc, low-K tholeiitic magma.